Effect of farmyard manure and humic acid on growth and yield of rice (Oryza sativa L.) - Bera, B; Bokado, K; Barkha; Bag, A G; Naga, T T R (Plant Science Today, 2024)
The research work was established to determine the effect of farmyard manure (FYM) and humic acid (HA) on growth, yield, and soil chemical properties for the sustainable production of rice. The experiment was performed in the Kharif season of 2023 at the Agronomy Farm, School of Agriculture, Lovely Professional University in Phagwara, Punjab. The Split-plot design was used to set up the experiment, which consisted of sixteen treatment combinations that were replicated thrice. The main plots included four levels of FYM (0, 5, 10, and 15 t ha-1), while the subplots comprised four levels of humic acid (0 %, 2 %, 3 %, and 4 %). The incorporation of FYM at 15 t ha-1 with a foliar spray of 4 % humic acid effectively increased growth attributing characteristics (plant height, number of tillers hill-1, root-to-shoot ratio, plant dry weight, crop growth rate, and relative growth rate) and yield of the rice compared to the other levels of farmyard manure and humic acid. Additionally, FYM significantly improved soil chemical properties such as organic carbon, available nitrogen, available phosphorus, and available potassium, whereas foliar sprays of humic acid did not significantly enhance soil chemical properties. There was no interaction impact on soil chemical status. However, incorporating 15 t ha-1 FYM with a foliar spray of 4 % humic acid together could be the best nutrient management practice for long-term sustainable rice production and maintaining soil chemical properties.